A short note on the noncoprime regular module problem - Ercan, G.; Güloğlu , Ş. (Ukrains’kyi Matematychnyi Zhurnal, 2020)
UDC 512.5 Considering a special configuration in which a finite group A acts by automorphisms on а finite group G and the semidirect product GA acts on the vector space V by linear transformations, we discuss the existence of a regular A-module in V_A .